DEVELOPMENT OF SUBSYSTEM SOFTWARE FOR RESEARCH OF EXPERIMENTAL CONSTRUCTIONS FOR THE FEMUR REINFORCING - Prokopovich, І.; Savelyeva, O.; Starushkevych, T. (Odes'kyi Politechnichnyi Universytet. Pratsi, 2020)
Bone reinforcement is one of the most effective surgical interventions. In addition, development, improvement and production of implants aimed at creating high quality, reliable structures that can retain their functional properties for a long time. One of the most important stages in the development and design of implantable power structures is the biomechanical justification of their performance and reliability. The article presents the development and testing of a software subsystem for the study of experimental structures for preventive reinforcement of the femur, as well as the study of the peculiarities of the creation of such systems. The design subsystem, which is proposed in the article, is an auxiliary module for Ansys software, written in the Python programming language in the PyScripter environment. It allows you to build a qualitative picture of the stress-strain state in a selected volume of the femoral neck, to refine the grid of finite elements and set boundary conditions, which in turn used for mathematical calculation of the stress state. The study includes the calculation of stress states in the intact bilayer bone to identify critical points of onset of destruction of the cortical layer of bone. The created calculation module facilitates interaction with the software, allowing specifying more precisely necessary conditions of carrying out experiment. Based on the results obtained during the experiments, we can conclude about the usefulness of using both the created module and the created models. The results of the numerical experiment show better characteristics of the reinforced bone in contrast to the intact.